Realizing healthy homes through the latrine program in Meteseh Village Semarang Indonesia - Mutiawati Mandaka; Gatoet Wardianto; Taufiq Rizza Nuzuludin (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
A place of shelter and rest that fulfils physiological needs fulfils psychological needs, prevents disease transmission, prevents accidents and fulfils the concepts of cleanliness, health and beauty that can lead to a perfect life, both physically, spiritually and economically, is called a healthy home. Its characteristics include having a good water source, smooth air circulation inside and outside the room, solid and liquid waste disposal channels, freeing harmful chemicals, house cleanliness, sturdy building materials, and a green environment. Basically, housing is a basic human need and is also a determinant of public health. Decent housing for housing must meet health requirements, one of which concerns the need for latrines. The purpose of this paper is to provide insight to the Meteseh community regarding healthy homes and provide solutions for people who do not meet healthy home standards. In Meteseh Village, there are still houses that do not have latrines. This time, the types of community service programs were in the form of counselling and demonstrations. The method used was by coordinating with the village head in Meteseh, Tembalang District, Semarang, conducting field surveys, asking permission to socialize with residents regarding healthy homes, then installing latrines and evaluating after latrine installation. This activity's target is poor and has not implemented a clean and healthy lifestyle in Meteseh village. The result after the service is that the Meteseh community understands a healthy home better and also begins to apply it in their daily lives.